Analisis Pengaruh Keberagamaan Terhadap Kualitas Kerja Karyawan BPRS Harta Insan Karimah Kantor Cabang Karawaci Kota Tangerang - Muizzudin, Muizzudin (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
As a part of sharia bank, BPRS Harta Insan Karimah plays an important role in empowering muslims and small and medium enterprises in rural areas. In playing its rule, the bank has to show the power of its employees especially in their religiosity and quality of work. This quantitative research is aimed at identifying the present existing data on their religiosity and quality of work and measuring the impact of their religiosity on their quality of work. The primary data is collected from the respondents’ responses to the statements of their religiosity as the independent variable and their quality of work as the dependent variable in the form of Likert scale options provided in the questionnaire. After going through the tests of validity, reliability, normality, and linearity, the data is processed to the regression analysis with SPSS 25. The results show that the religiosity as the independent variable has the positive impact on the quality of work as the dependent variable with the value of 12,8 %. This value is relatively small due to the fact that the research only uses one independent variable.